PENDAMPINGAN PENGGUNAAN APLIKASI SIAK TERINTEGRASI BUMDES BERKAH BERSAMA - Savitri, Enni; andreas, andreas; Diyanto, Volta; Musfialdy, Musfialdy; Hamzah, Amir (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
Village-owned businesses (BUMDes) are crucial to the empowerment of local residents and the growth of the community. BUMDes is crucial to developing a robust local economy, enhancing the welfare of rural communities, and fostering an inclusive and sustainable environment. The goal of the service activity is to help people use the BUMDes Berkah Bersama Integrated SIAK Mobile Application at BUMDes Berkah Bersama in the Indragiri Hulu Regency in order to boost village income, strengthen the village economy, and enhance the welfare of village communities. This service is being implemented using a technique that aids in the Web-based BUMDes business unit management system implementation. Through a variety of evaluation techniques, including surveys, interviews, data analysis, and direct observation, the degree of achievement of the program objectives is assessed. This program, which provides guidance for web-based BUMDes financial reporting, helps villages become more prosperous while also enhancing their financial management and giving their communities more authority. In this approach, the initiative can be viewed as a concrete example of civic engagement for enhancing welfare and sustainable growth in rural communities.